2018
DOI: 10.1002/cche.10054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tempering moisture and infrared heating temperature on the functionality of Desi chickpea and hull‐less barley flours

Abstract: Background and objectives:The effect of seed tempering moisture (20% moisture content or left un-tempered) and infrared heating surface temperature (115 or 135°C) on the functional properties of Desi chickpea and hull-less barley was investigated. Findings: Tempering and infrared heating reduced the protein solubility in both flours, whereas the ability to bind oil was unaffected. Both flours had increased water binding abilities in response to tempering and infrared heating. In the case of chickpea flour, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 34 publications
2
16
2
Order By: Relevance
“…Maize flour and all its precooked flours did not form foams. FA for unprocessed chickpea (~217%) and sorghum (~117%) reported by Bai et al () and Elbaloula, Yang, Guo, and Gu (), respectively, agrees with this study. Akubor and Onimawo () reported that FA of maize flour was 4%, the slightly greater FA compared to the results in this study could be due to the higher protein content (~9%) of their maize flour.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Maize flour and all its precooked flours did not form foams. FA for unprocessed chickpea (~217%) and sorghum (~117%) reported by Bai et al () and Elbaloula, Yang, Guo, and Gu (), respectively, agrees with this study. Akubor and Onimawo () reported that FA of maize flour was 4%, the slightly greater FA compared to the results in this study could be due to the higher protein content (~9%) of their maize flour.…”
Section: Resultssupporting
confidence: 92%
“…If protein solubility is poor, less protein can migrate to the interface and no stable foam can be developed. Decreased foaming capacity has been reported for tempered chickpea (20% moisture) flour when heated at 115 and 135°C (Bai et al, ). The absence of FA and FS for all the precooked flours in this study implies that extrusion probably rendered a combination of low protein solubility, protein denaturation, and thus poor protein migration to the air–water interface to support foam formation.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations